Comparative capital punishment - Steiker, Carol S.; Steiker, Jordan M. (Research handbooks in comparative law, 2019)
Comparative Capital Punishment offers a set of in-depth, critical and comparative contributions addressing death practices around the world. Despite the dramatic decline of the death penalty in the last half of the twentieth century, capital punishment remains in force in a substantial number of countries around the globe. This research handbook explores both the forces behind the stunning recent rejection of the death penalty, as well as the changing shape of capital practices where it is retained. The expert contributors address the social, political, economic, and cultural influences on both retention and abolition of the death penalty and consider the distinctive possibilities and pathways to worldwide abolition.